An empirical analysis of online shopping behavior in India: a demographic perspective / Sonia Bhatt - Bhatt, Sonia (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA (UiTM) Shah Alam, 2019)
The e-commerce market of the world is growing at a very fast rate. High internet access rate, increased smart-phone users’ rate, growing mobile internet users’ rate, reduced smart-phone cost and added internet speed has enabled online shopping too much user-friendly and easier in recent years. The purpose of this paper is to investigate the role of demographic variables of the customers in affecting online shopping behavior. With the help of an extensive literature review, hypotheses were formulated for seven demographic variables i.e. age, gender, marital status, location, level of education, income per month and occupation. With the help of a survey method 542 responses were collected from three different locations New Delhi, Gorakhpur and Mumbai. A chi-square test was performed for checking the association between demographic variables and attitude of online shoppers towards online shopping. A significant positive association was observed between level of education and level of income with the online shopping behavior of the consumers. Based on the empirical findings, this paper includes managerial suggestions for stimulating online shopping behavior among consumers.